One-step construction of Y, C, and O tridoped g-C3N4 as a bifunctional photocatalyst for H2 evolution and organic pollutant degradation under visible light irradiation. Issue 16 (2nd August 2022) - Hassan, Ahmed E.; Hussien, Mai S. A.; Elsayed, Mohamed Hammad; Mohamed, Mohamed Gamal; Kuo, Shiao-Wei; Chou, Ho-Hsiu; Yahia, Ibrahim S.; Wang, Genxinag; Wen, Zhenhai
Abstract : We successfully synthesized a series of Y, C, O tridoped g-C3 N4 photocatalysts using a simple one-step thermal polymerization method as a bifunctional photocatalyst for H2 production and pollutant degradation under visible-light irradiation. Abstract : Photocatalytic H2 production and degradation of pollutants are promising strategies for energy conversion and environmental protection, where highly efficient photocatalysts are required. Herein, a novel type of Y, C, and O tridoped g-C3 N4 bifunctional photocatalyst was prepared via a simple one-step low-cost thermal polymerization technique, which exhibits a significant enhancement in photocatalytic redox efficiency under visible light for H2 production and degradation of pollutants compared to bulk g-C3 N4 . The optimized Y0.1/C/O tridoped g-C3 N4 photocatalyst exhibits a remarkable H2 evolution rate (HER = 2542.4 μmol g −1 h −1 ) which is 5 times higher than that of pristine g-C3 N4 with a high apparent quantum yield of 6% at 420 nm, besides excellent degradation efficiencies for organic pollutants (∼100, 98.5 and 82.4% for mixed dyes, congo red, and methylene blue, respectively). The influence of Y 3+ concentration on the photocatalytic performance and electronic structure of Y/C/O–CN was also investigated. The major reactive species involved in the photodegradation process were found to be superoxide (O2 ˙ − ) radicals. Moreover, the experimental and computational results suggest that the enhanced photocatalytic performance is due to the synergistic effect of Y, C, and O tridoping, which can adjust the band structure of g-C3 N4, reduce the bandgap, improve visible-light absorption, and accelerate charge separation. This study paves the way to fabricate extremely effective tridoped photocatalysts for efficiently evolving hydrogen under visible light and resolving future environmental pollution.